Efektivitas Penerapan Aplikasi Bursa Kerja Online di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Solok - Yulia Khairunnisa; Hasbullah Malau (Policy, Law and Political Research Center, 2022)
This study aims to determine the effectiveness of the application of the Online Job Exchange (BKOL) application at the Solok City Investment and One-Stop Integrated Service Office, and the supporting and inhibiting factors in the application of the Online Job Exchange application at the Investment Office and One Stop Services in Solok City. This research was conducted in Solok City using qualitative analysis techniques with descriptive methods withi, interviews, obserpations and documentation studies. The results of this study indicate that the Effectiveness of the Application of the Online Job Exchange application at the DPMPTSP Solok City according to the indicators, it can be said that three indicators are generally effective including satisfaction with the program, achievement of goals, input and output levels, while overall, target success, input and output levels, and satisfaction with the program in general its implementation has not been effective. The supporting and inhibiting factors in the Application of the Online Job Exchange Application of the Investment Service One Stop Service in Solok City consist of two, namely internal obstacles in the form of the absence of cooperation between DUKCAPIL and DMPTSP, such as when job introduction officers enter the NIK of unregistered job seekers, and external in the form of low public understanding in the use of this application, it can be seen that there are still job seekers who choose to come to the Solok City DMPTSP office.